THE RELATIONSHIP OF THE CHARACTERISTICS OF ANTI-EPILEPSY DRUGS WITH THE C OGNITIVE FUNCTION OF EPILEPSY PATIENTS - Handayani, Sri; Partan, Radiyati Umi; Hafy, Zen; Octaviana, Fitri; Harun, Yusril; Bahar, Erial; Lestari, Nova (MNJ (Malang Neurology Journal), 2025)
Background: One of the side effects of the use of antiepileptic drugs (AEDs) is cognitive disorder. Several studies show a relationship between the type of AEDs and cognitive disturbance in people with epilepsy. Dose-dependent side effects of AEDs have also been reported in prior research. However, there are results from different studies on different populations. Objective: This research aims to evaluate the relationship between AEDs characteristics and the cognitive function of epilepsy patients. Methods: This cross-sectional study was conducted in the Neurology Department of Dr. Mohammad Hoesin General Hospital Palembang, from 1 November 2021 to 31 March 2022. Researchers used the MoCA-Ina questionnaire to collect medical record data and conduct interviews. Results: In this research, the number of research subjects obtained was 70 people with epilepsy. Characteristics of sociodemographic sufferer Epilepsy in this study was mostly (44.3%) aged 26 – 45 years with type sex most were women (71.4%), and the majority subjects (52.9%) had level high school education. Characteristics of antiepileptic drugs consumed by people living with epilepsy: most of them, i.e., amounting to 57.1%, have consumed antiepileptic drugs for > 12 months. Most of the research subjects (64.3%) had function-impaired cognitive range MoCA-Ina scores of 8 – 30. The function most cognitively disturbed, namely in the memory domain, cancels that am, counting to 82.9%. Education level is the only variable from characteristics of sociodemographic and clinical features connected significantly to cognitive function in general (p-value 0.013). The number, duration, and type of antiepileptic drugs do not determine a significant relationship with cognitive function in general. Conclusion: There is a significant relationship between valproic acid and the number of AEDs with the naming domain, as well as between valproic acid and the duration of AEDs with the abstraction domain.